THE BASIC TYPES OF TRANSLATION AND EQUIVALENCE IN TRANSLATION - Abduraxmanova Zilola Yoqubjon qizi; Qodirova Iroda Ulug`bek qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the fundamental types of equivalence in translation, a critical concept that underpins the process of transferring meaning between languages. It delineates four primary types: formal equivalence, which emphasizes a close adherence to the original text’s structure and content; dynamic equivalence, which focuses on conveying the thought and emotional weight of the original; cultural equivalence, which adapts messages to fit the cultural context of the target audience; and textual equivalence, which considers the relationship between entire texts rather than isolated phrases. Each type of equivalence serves distinct purposes and is applicable in various contexts, from legal documents to literary works. Understanding these types enhances the translator’s ability to maintain accuracy, relevance, and engagement in their translations, ultimately fostering effective crosscultural communication.